Sistem OZN in (inter)regionalizem - Bojinović Fenko, Ana (Teorija in praksa, 2016)
This article shows the impact of regional and interregional cooperation in the international community on the functioning of the UN system. The research question is whether the action of regions is complementary or competitive with regard to the global level of international relations (the UN system). A historical analysis of the evolution of rules defining the conditions for regionalism is followed by an analysis of UN member states' functioning in the UN system within regional groupings. This is followed by an examination of the influence of regions on the UN system directly and through interregionalism. The author concludes by establishing that the performance of countries at the regional level shows complementarity, and also occasionally competition, with the UN system, and she presents proposals to strengthen the first and overcome the second.
Keywords: International community; International organizations; International relations; Mednarodna skupnost; Mednarodne organizacije; Mednarodni odnosi; OZN; Regionalism; Regionalizem